Verifying end-to-end real-time constraints on multi-periodic models - Forget, Julien; Boniol, Frederic; Pagetti, Claire (2017 22nd IEEE International Conference on Emerging Technologies and Factory Automation (ETFA), 2017)
Control-command systems must usually satisfy a set of high-level end-to-end timing constraints to ensure their correctness. We propose a formal approach to verify these properties directly at the model level. First, we introduce a small language for specifying arbitrary end-to-end constraints. Then, we show how to verify any constraint of this language for a system represented with a multi-periodic synchronous model, a model that retains the main concepts of data-flow oriented programming languages (such as Matlab/Simulink, synchronous languages or AADL). One advantage of this approach is that it is simpler to verify end-to-end constraints at the model level, early in the development process, rather than at the implementation level.